Influence of Different Substrates on the Production of a Mutant Thermostable Glucoamylase in Submerged Fermentation - Pavezzi, Fabiana Carina [UNESP]; Jacomassi Carneiro, Andreia A. [UNESP]; Bocchini-Martins, Daniela Alonso [UNESP]; Alves-Prado, Heloiza Ferreira [UNESP]; Ferreira, Henrique [UNESP]; Martins, Paula M. [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (Humana Press Inc, 2011)
Three mutations, Ser54 -> Pro, Thr314 -> Ala, and His415 -> Tyr, were identified in Aspergillus awamori glucoamylase gene expressed by Saccharomyces cerevisiae. The mutant glucoamylase (GA) was substantially more thermostable than a wild-type GA at 70 A degrees C, with a 3.0 KJ mol(-1) increase in the free energy of thermo-inactivation. The effect of starch from different botanical sources on the production of this GA was measured in liquid fermentation using commercial soluble starch, cassava, potato, and corn as the carbon source. The best substrate for GA production was the potato starch showing an enzymatic activity of 6.6 U/mL. The commercial soluble starch was also a good substrate for the enzyme production with 6.3 U/mL, followed by cassava starch and corn starch with 5.9 and 3.0 U/mL, respectively. These results showed a significant difference on GA production related to the carbon source employed. The mutant GA was purified by acarbose-Sepharose affinity chromatography; the estimated molecular mass was 100 kDa. The mutant GA exhibited optimum activity at pH 4.5 and an optimum temperature of 65 A degrees C.
Keywords: Mutant glucoamylase; Thermostable enzyme; Production; Purification; Corn starch; Potato starch; Cassava starch; Thermo-inactivation